High rock content enhances plant resistance to drought in saline topsoils - Lison, Christine; Cross, Adam; Stevens, Jason; Valliere, Justin; Dixon, Kingsley; Veneklaas, Erik (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2021)
Successful mine site restoration in semi-arid regions is limited by availability of topsoil and water, and saline soils are a common feature of these regions and pose an additional stressor to vegetation establishment. We tested the growth and development of a salt-tolerant species on saline topsoil incorporating 25%, 50%, 75% and 88% waste rock, examining soil water content and plant water use to determine how waste rock content affected plant-water relations, growth and development. Under well-watered conditions higher percentages of waste rock lowered the volumetric water content of the total soil mix, causing a reduction in stomatal conductance. Under drought conditions, higher waste rock content reduced rates of water loss and allowed stomatal conductance to be maintained over a longer period. There was no significant or optimal relationship between waste rock content and plant growth, indicating that the addition of waste rock to topsoil has complex effects on plant-water relations and growth. We demonstrate that augmentation of limited topsoil resources with waste rock is a promising option for improving plant resistance to drought in mine site restoration.